Legal Assistance in the Preparation of Padangsambian Grassroots Festival Competition Regulations - SANCAYA, I Wayan Werasmana; I Gede Wira DARMA; IB Gede Agustya MAHAPUTRA; I Made Aditya Mantara PUTRA (PT Batara Swastika Harati, 2025)
The legal assistance program for drafting regulations of the Padangsambian Grassroots Festival was conducted to strengthen the governance of community-based football competitions through a participatory legal approach with a child protection perspective. A common phenomenon found at the community level is the absence of written regulations, which leads to potential conflicts, uncertainty in referee decisions, and weak protection of young players. Using the community-based legal drafting method, this program involved organizers, coaches, participants, and parents in drafting adaptive regulations with social legitimacy. The results indicate an increase in community legal awareness and the establishment of a regulation document that includes child protection clauses, dispute resolution mechanisms, and the formation of a Match Ethics Committee as a structured mediation body. This initiative also produced a significant social impact by reinforcing a culture of deliberation and legal literacy within the local sports community. The approach has proven effective and is recommended for replication by other grassroots sports communities as a model of participatory legal governance in amateur competitions.